HUBUNGAN PENGETAHUAN IBU TENTANG MP-ASI DENGAN WAKTU PEMBERIAN MP-ASI PADA BAYI DI KLINIK CINDY KEC. KABANJAHE - Selvia Yolanda Dalimunthe, Endang Sihaloho, Mery Krista Simamora (JURNAL PIONIR, 2021)
ABSTRACTThe provision of complementary foods for breastfeeding is the provision of food or drinks containing nutrients that are given to infants or children aged 6-24 months to meet their nutritional needs. Giving solid or additional foods that are too early can interfere with exclusive breastfeeding and increase morbidity in infants. The purpose of this study was to analyze the relationship between mother's knowledge of complementary foods and the timing of giving complementary foods to infants. The research method used in this research is correlation analytic with cross sectional approach. This research was conducted at Cindy Clinic, Kec. Kabanjahe from January 2021 to June 2021. The population of the study is mothers who have babies at Cindy's clinic with a sample of 85 people, using purposive sampling technique. Data was collected by distributing questionnaires. Data analysis using Chi-square test. The results showed that there was a relationship between mother's knowledge of complementary foods and the timing of giving complementary foods to infants at the clinic. Cindy Kec. Kabanjahe with p-value 0.000. Respondents are expected to further increase knowledge related to MPASI with the timing of giving MPASI. Keywords: Knowledge, timing of complementary feeding, Infants